Efficacy and safety of mavrilimumab in Japanese subjects with rheumatoid arthritis: Findings from a Phase IIa study. Issue 1 (January 2015) - Takeuchi, Tsutomu; Tanaka, Yoshiya; Close, David; Godwood, Alex; Wu, Chi-Yuan; Saurigny, Didier
Abstract Objective. A phase IIa study investigated efficacy and safety/tolerability of ascending doses of mavrilimumab (anti-granulocyte-macrophage colony-stimulating factor receptor [GM-CSFR]α monoclonal antibody) in adult subjects with moderate to severe rheumatoid arthritis from Japan and Europe. Findings from the Japanese population are presented. Methods. Fifty-one subjects received mavrilimumab (10–100 mg) or placebo subcutaneously every other week for 12 weeks, followed by a 12-week follow-up period. The primary endpoint was the proportion of subjects achieving a Disease Activity Score using 28 joints (DAS28)-C-reactive protein (CRP) response (decrease > 1.2 from baseline). Secondary endpoints included DAS28-CRP remission, Health Assessment Questionnaire Disability Index (HAQ-DI) and American College of Rheumatology (ACR) response. Results. By Week 12, more mavrilimumab- versus placebo-treated subjects achieved a DAS28-CRP response (50.0% vs. 23.5%, p = 0.081); a significant response was seen in the 30 mg and 100 mg dose groups (both 75.0% vs. 23.5%, p = 0.028). The 100 mg group also demonstrated statistically significant HAQ-DI and ACR20 responses at Week 12. Results were generally consistent between Japanese and European populations. Overall, adverse events (AEs) were mild to moderate in intensity with one serious AE of pneumonia, considered possibly treatment-related. Conclusions. A rapid and clinically meaningful response was seen in subjects treated with GM-CSFRα blockade with mavrilimumab, supporting further investigation of mavrilimumab for the treatment of RA in Japanese subjects.